Anharmonic phonon interactions and the Kondo effect in a FeSe/Sb2Te3/FeSe heterostructure: a proximity effect between ferromagnetic chalcogenide and di-chalcogenide. Issue 30 (18th July 2022) - Ghosh, Labanya; Alam, Mohd; Singh, Mahima; Dixit, Srishti; Kumar, Satya Vijay; Verma, Abhineet; Shahi, Prashant; Uwatoko, Yoshiya; Saha, Satyen; Tiwari, Archana; Tripathi, Ajay; Chatterjee, Sandip
Abstract : A FeSe/Sb2 Te3 /FeSe heterostructure establishes the signature of the Kondo effect and a spin–phonon coupling initiated by local charge ordering at the interfaces. Abstract : In this report, we have introduced magnetic ordering into the nontrivial system of conventional topological insulators (TIs) by creating magnetic interfaces. In this context, antimony di-chalcogenide Sb2 Te3 sandwiched between two thin layers of FeSe was prepared using the pulsed laser deposition (PLD) technique. The prepared heterostructure demonstrated good crystallinity along with homogeneous morphology displaying pyramid-shaped characteristic triangular islands. To comprehend the temperature and magnetic field modulated inter-layer properties of the prepared hetero-structure, transport, magneto-transport and magnetic properties were investigated. These properties establish the signature of the Kondo effect below 15 K, which has been attributed to the antiferromagnetic spin alignment in that temperature range. At around 150 K, longitudinal and transverse resistivity shows the metal–semiconductor transition, which was further elucidated through the anharmonic decay model in vibration phonon modes using Raman spectroscopy. Furthermore, a significant local spin evolution was explored at around 475 K by studying the magnetic properties of the system. The temperature dependency of the Raman modes confirmed the spin–phonon coupling initiated by local charge ordering at the proximity of the interface in the prepared hetero-structure.